APPLICATION OF MATHEMATICAL MODELING IN THE EVALUATION OF IN VITRO DRUG RELEASE - N. I. Filippova; A. A. Teslev (Разработка и регистрация лекарственных средств)
Descriptions of mathematical models using for drug dissolution studying from modified-release systems (zero-order kinetic, first-order kinetic, Weibull model, Hixon - Crowell model, Higuchi model, Baker - Lonsdale model, Hopfenberg model, Gompertz model, Korsmeyer - Peppas model, Peppas - Sahlin model) were presented in the article. Results of ibuprofen release from carbomer matrix tablets were processed using Higuchi and Korsmeyer - Peppas models.